Case Report: Could genetic factors influence the outcomes of first-line enfortumab vedotin plus pembrolizumab therapy in patients with metastatic urothelial carcinoma? Two cases of patients harbouring a BRCA mutation - Salfi, Giuseppe; Clerici, Chiara Maria Agrippina; Pecoraro, Giovanna; Pedrani, Martino; Puglisi, Marialuisa; Tortola, Luigi; Pereira Mestre, Ricardo; Vogl, Ursula; Colombo, Ilaria; Barizzi, Jessica; Frattini, Milo; Graffeo, Rossella; et al. (Frontiers in Oncology, 2025)
The introduction of enfortumab vedotin combined with pembrolizumab (EV-P) as a first-line treatment for advanced urothelial carcinoma (UC) has transformed the therapeutic landscape and holds great promise for improving patient outcomes. However, predictive and prognostic biomarkers for this novel regimen remain limited, and no specific subgroup has yet been identified for whom frontline EV-P could be withheld in favor of platinum-based chemotherapy. We report the first two cases of patients with BRCA-mutant metastatic UC who experienced markedly short progression-free survival with first-line EV-P but achieved more durable responses with second-line platinum-based chemotherapy. These observations raise important questions about the potential predictive role of BRCA - and more broadly, DNA damage repair - mutations in the evolving treatment paradigm of UC. Given the known sensitivity of BRCA-mutated tumors to platinum agents, frontline platinum-based chemotherapy may warrant consideration in this molecularly defined subgroup. Larger studies are needed to validate these preliminary findings and inform treatment selection.